Improving Activity and Learning Mathematics Through Strategies Teams Games Tournaments for Students Of Class IV SDN Sambirejo 4 - Laksono, Ari Tejo (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to improve mathematics learning outcomes about the concept of integer arithmetic operations in fourth grade students of SD Negeri Sambirejo 4 Sambirejo District for the 2019/2020 academic year. This study uses a Classroom Action Research (CAR) model which is carried out in 2 cycles. The results showed that there was an increase in student activity and learning outcomes using the Teams Group Tournament strategy. In the pre-cycle stage of 24 students who achieved learning completeness 10 students (41.7%). Then in the first cycle of learning completeness reached 16 students (66.7%) and in the second cycle there was an increase to 18 students (75%). So the conclusion of this study shows that learning with the Teams Group Tournament strategy improves mathematics learning outcomes for fourth grade students at SD Negeri Sambirejo 4, Sambirejo District, 2019/2020 Academic Year